2011
DOI: 10.1002/andp.201100006
|View full text |Cite
|
Sign up to set email alerts
|

The most general ELKO matter in torsional f(R)‐theories

Abstract: We study f (R)-gravity with torsion in presence of the most general ELKO matter, checking the consistency of the conservation laws with the matter field equations; we discuss some mathematical features of the field equations in connection with a cosmological application.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 35 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…[10][11][12][13][14][15] For instance, possible applications of ELKO spinor fields to more general f (R) gravitational theories. 16 The formal aspects about the inequivalent spin structures in spacetime in terms of the different possible spin connections [17][18][19] have resulted prominent physical applications. We investigate dark spinor fields in spacetimes with non-trivial topologies, in order to clarify how the dynamics of such dark spinor fields can be used as a tool for probing the metric spacetime structure, related to a non-trivial topology itself.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] For instance, possible applications of ELKO spinor fields to more general f (R) gravitational theories. 16 The formal aspects about the inequivalent spin structures in spacetime in terms of the different possible spin connections [17][18][19] have resulted prominent physical applications. We investigate dark spinor fields in spacetimes with non-trivial topologies, in order to clarify how the dynamics of such dark spinor fields can be used as a tool for probing the metric spacetime structure, related to a non-trivial topology itself.…”
Section: Introductionmentioning
confidence: 99%
“…Elko in the presence of torsion has been a subject of several insightful papers by Luca Fabbri. We refer the reader to these and related publications [93][94][95][96][97][98][99]. Cosmological solutions of 5D Einstein equations with Elko condensates were obtained by Tae Hoon Lee where it was found that there exist exponentially expanding cosmological solution even in the absence of a cosmological constant [100].…”
mentioning
confidence: 99%
“…Incursions into the world of fashion by artists continued with Street art, Graffitism, and Pop Art. Keith Haring painted fabrics, T-shirts, and watches for Vivienne Westwood, and his collaboration with Elio Fiorucci in Milan was instrumental in the opening of his emporium in San Babila (Fabbri F., Muzzarelli F. 2011).…”
Section: Fashion and Artmentioning
confidence: 99%